Unlawful dismissal of the administrators of courts - Piebiak, Łukasz (Finding a way out of Poland’s rule-of-law crisis: Possible courses of action and reform, 2026)
Chapter Two describes the unlawful dismissal of court presidents by the Ministers of Justice after December 13, 2023. The author points to deliberate personnel manipulations and the disregard for the statutory requirement to obtain both the opinions of court boards and the consent of the National Council of the Judiciary (KRS). In response to these actions, the Constitutional Tribunal (case K 2/24) ruled these practices unconstitutional. As a result of the ruling, no legal procedure currently exists to dismiss a court president without their consent. The author advocates for declaring the completed dismissals legally ineffective and reinstating the judges to their positions. However, to protect legal certainty, administrative and personnel decisions made by the newly appointed presidents should remain in force. In the conclusion, the author calls for an urgent statutory amendment and the implementation of the Tribunal's ruling. New regulations must guarantee the real participation of the KRS in the process and permanently block the executive branch from arbitrarily interfering in court leadership.